Systems theory and management of organization - Sharma, C. L. (Philippine Journal of Public Administration, 1990)
Systems theory is considered to be a major reorientation in scientific thinking during the last few decades. It purports to replace the analytical and atomistic modes of inquiry by holistic and integrative ones. It offers a sophisticated, fascinating and impressive theoretical construct but is deficient in commensurate applicability to real situations. Management of organizations would remain an exasperating, frustrating, and challenging task; and experience, intuition, and judgment would continue to play an important role. Nonetheless, systems theory represents an attempt toward developing the science of management.